The Influence of Work Culture and Discipline on Employee Work Effectiveness at PT. Bank Sulteng Tolitoli Branch - Julianti; ayuwandira m. morad; Moh. Sabaran (LPPM STIE Mujahidin Tolitoli, 2026)
Companies employ various strategies to enhance employee work effectiveness; among these, work discipline and work culture play a pivotal role in improving efficiency and effectiveness in executing planned and programmed activities. This study aims to determine the effect of work culture and discipline on work effectiveness at PT. Bank Sulteng Tolitoli Branch. This research utilizes a quantitative approach with primary data sources. Data collection methods were conducted through observation, questionnaires, and documentation. The data analysis methods employed include multiple linear regression analysis, coefficient of determination (R^2), data quality testing via validity and reliability tests, and hypothesis testing using the t-test and F-test. The sampling method applied was saturated sampling (census). The results of this study indicate that work culture has no positive and non-significance effect on work effectiveness at PT. Bank Sulteng Tolitoli Branch. Furthermore, statistical analysis demonstrates that work discipline has a positive and significant effect on work effectiveness at PT. Bank Sulteng Tolitoli Branch. Concurrently, work culture and discipline simultaneously exert a positive and significant effect on work effectiveness at PT. Bank Sulteng Tolitoli Branch.